Fundraiser for Ron Gonzales. - Sahl, Ted (photographer):::Creator::::::::::::
Jon Snell hosts a fundraiser for Ron Gonzales's campaign for Santa Clara County Supervisor. Group photo shows (left-to-right) John Laird, Alvina Gonzales, Ron Gonzales, Sal Accardi, Susan Hammer and Jon Snell. .